Effects of short-term creatine supplementation for a simulated basketball tournament - Fausett,W. A.; Stephens, K. R.; Hopkins, W. G. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Creatine supplementation is considered to enhance performance of repeated bouts of high-intensity exercise. We have therefore determined the effect of creatine supplementation for a simulated basketball tournament. The study was a double-blind randomized crossover, in which 6 male and 6 female elite basketball players completed a tournament consisting of one simulated game per day for three consecutive days. For five days prior to the first game, half the subjects ingested 0.1 g of creatine per kg of body mass, dissolved in 250 ml of an 8% carbohydrate sport drink, 4 times per day. They ingested a maintenance dose of 0.04 g/kg during the tournament. The other subjects consumed a placebo (glucose) in the same manner. After a washout period of 28 d, subjects crossed over for the creatine and placebo treatments and repeated the tournament. Results from a time-motion study of Australian elite male basketballers were used to design the simulated game, which consisted of a 10-min warm up followed by eight ~5-min circuits with rests of 0.5-5 min between circuits. Each circuit consisted of three maximal 20-m shuttles, five submaximal 40-m shuttles, one maximal and three submaximal defensive shuffles, one set of 10 maximal jumps, and one goal-shooting activity in a fixed order. Performance was recorded for maximal activities and goal shooting. Blood samples were collected at regular intervals for measurement of lactate concentration. Repeated-measures mixed modeling was used to analyze effects as percent change (with 95% likely range). Creatine increased body mass by 0.9% (0.5 to 1.2%), presumably by increasing fluid retention in muscle cells. Creatine decreased blood lactate by 0.4 mmol.L-1 (-0.2 to 1.0 mmol.L-1), which is consistent with less use of the anaerobic glycolytic pathway to meet energy demands. There was little effect on performance averaged over the tournament, but during the tournament (Day 3 minus Day 1) creatine produced the following effects relative to placebo: from start to finish of a game, jump height increased 8.5% (-3.0 to 20%), shuffle speed increased 5.1% (0.4 to 9.9%), but sprint speed decreased 2.7% (-0.2 to 5.7%); successful goal shooting with creatine also increased 9.7% (2.9 to 17%) by Day 3, although with creatine shooting percentage was substantially lower on Day 1. This change in goal-shooting success was unexpected and warrants further study. Creatine appears to improve some measures of performance of elite basketball players during a game on the last day of a simulated tournament relative to the first day. However, creatine has negligible effect on average performance over a tournament, so it is probably not a beneficial supplement for basketball and similar high-intensity sports.